Boron and zinc application on soil as complement to leaf spray on orange Pera trees - Quaggio, José Antônio; Junior, Dirceu Mattos; Cantarella, Heitor; Junior, Aprigio Tank (Pesquisa Agropecuaria Brasileira, 2003)
Boron (B) and zinc (Zn) are the most deficient micronutrients in the Brazilian's citrus industry. Worldwide, there is limited information about diagnostic criteria and management of these nutrients to the citrus crop. Leaf spray has been the usual form of application of these nutrients, despite their low redistribution into the citrus trees. The present work was carried out during four years in order to establish responses of citrus yield to complementary soil application of B and Zn compared to the traditional leaf spray, and to improve diagnostic tools for micronutrient recommendation based on soil and leaf analyses. The experiment was a 42 factorial design, with three replications, with four yearly rates (0, 2, 4 and 6 kg ha-1) of B, as boric acid, and Zn, as zinc sulfate. A significant response to soil B application was observed in two years compared to the conventional spray treatment, which did not improve yield and fruit quality. Maximum yield was reached at 4 kg ha-1 B rate, which increased the hot-water extracted soil-B to 1.0 mg dm-3, and total leaf-B to 300 mg kg-1. Soil Zn application was less effective than the leaf spray treatment due to high Zn adsorption in the soil. Soil testing and leaf analyses calibration curves were determined to establish B and Zn nutrient management program for citrus.